Association between periodontitis and the risk of palindromic rheumatism: A nationwide, population-based, case-control study. - Ching-Heng Lin (PLoS ONE, 2017)
To estimate the association between a history of periodontitis (PD) and the risk of incident palindromic rheumatism (PR).Using a nationwide, administrative database, this study identified 4,421 newly-diagnosed PR cases from 2007 to 2012 and randomly selected 44,210 non-PR controls matched (1:10) for sex, age and the year of the index date. After adjusting for comorbid diabetes mellitus, we estimated the odds ratios (ORs) with 95% confidence intervals (CIs) using conditional logistic regression analysis to quantify the association between a history of PD and the risk of PR. The influences of the lag time and severity of PD were examined by calculating ORs for subgroups of patients based on the time interval between the last PD-related visit and the index date and PD-related cumulative cost and number of visit.This study showed an association between a history of PD and incident PR (OR, 1.51; 95% CI, 1.41-1.61). The association remained significant after variation of PD definitions. The magnitude of the association was greater in those with shorter lag time between the latest date of PD diagnosis and PR index date and those who had a higher number of visits for PD or a greater cumulative cost for PD-related visits. After excluding 569 PR patients who developed rheumatoid arthritis after the index date, we found a consistent time- and dose-dependent association between PD and PR risk.This study demonstrated a time- and dose-dependent association between PD exposure and PR risk.